PENERAPAN METODE SIMA’I DALAM MEMPERKUAT HAFALAN AL-QUR’AN SISWA DI MTS MADINATUSSALAM MEDAN - Alfi Rahman Nasution (Prodi PAI Sekolah Tinggi Agama Islam Serdang Lubuk Pakam, 2024)
The objective of this study is to investigate the efficacy of the sima'i technique in enhancing students' memorization of the Al-Qur'an at MTs. Madinatussalam, as well as to identify the factors that contribute to this improvement. This study falls under the category of qualitative descriptive research. A variety of data acquisition methods were employed by the researchers, comprising documentation, interviews, and observation. The present study employs the interactive analytical method developed by Miles and Huberman. This method comprises four distinct phases: data acquisition, data condensation, data presentation, and verification/conclusion. Triangulation is the method utilised to guarantee the precision and dependability of the data. The findings of the study indicate that the sima'i technique implemented at Mts Madinatussalam Medan is executed in a sequential fashion, adhering to the instructor-established objectives. The scholars then commit the poems to memory. Furthermore, subsequent to the verses being effectively memorised, students are directed to engage in repetition of the just memorised material. Elements that contribute to memory improvement consist of motivation, intelligence, and overall health. Hence, it can be deduced that the implementation of the Sima'i technique at MTs Madinatussalam has the potential to significantly enhance the memorization of Al-Hal. This is demonstrated by the outcomes attained by pupils who implemented the Sima'i technique and successfully committed 30 Juz to memory.